1995
DOI: 10.1037/0022-0167.42.4.476
|View full text |Cite
|
Sign up to set email alerts
|

Client stages of change and expectations about counseling.

Abstract: The relation between client stages of change and client expectations about counseling was examined in a sample of 88 clients seeking services from a university-based outpatient clinic. Results of a canonical correlation indicated that the composite of the contemplation, action, and maintenance stages of change was significantly related to the expectation factors of Personal Commitment and Facilitative Conditions. The composite of the contemplation and maintenance stages of change accounted for additional varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
36
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 15 publications
5
36
1
Order By: Relevance
“…The differences observed between clients at the precontemplation stage, although statistically reliable, were modest. These results are consistent with prior research demonstrating a relationship between the precontemplation stage of change and expectations about counseling (Satterfield et al, 1995); results also indicate that there is a relationship between the precontemplation stage and premature termination (Smith et al, 1995). In addition, these findings are consistent with the theoretical perspective, outlined by McConnaughy, DiClemente, Prochaska, and Velicer (1989), that clients in the precontemplation stage seem to present a number of challenges that impede the progress of counseling.…”
Section: Discussionsupporting
confidence: 93%
“…The differences observed between clients at the precontemplation stage, although statistically reliable, were modest. These results are consistent with prior research demonstrating a relationship between the precontemplation stage of change and expectations about counseling (Satterfield et al, 1995); results also indicate that there is a relationship between the precontemplation stage and premature termination (Smith et al, 1995). In addition, these findings are consistent with the theoretical perspective, outlined by McConnaughy, DiClemente, Prochaska, and Velicer (1989), that clients in the precontemplation stage seem to present a number of challenges that impede the progress of counseling.…”
Section: Discussionsupporting
confidence: 93%
“…Our study replicates and extends the work of Satterfield et al (1995), who examined the relations among stages of change and expectations about counseling. Satterfield et al argued that given the impact of clients' expectations about counseling on the process and outcome of counseling (e.g., Heppner & Dixon, 1981) and people's decisions about whether to enter counseling (e.g., H. E. A.…”
mentioning
confidence: 52%
“…The current research replicated and extended the study by Satterfield et al (1995) by addressing several of the limitations in their study. First, Satterfield et al pointed out that participants in their sample were relatively young (mean age = 22.74 years, SD = 6.66).…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…A few studies provide evidence that a single continuous measure fits the data at least as well as a stage model (Budd & Rollnick, 1996;Satterfield, Buelow, Lyddon, & Johnson, 1995;Tsoh, 1995). Using a single continuous motivation score, the Project MATCH Research Group (1997) found that initial motivation for change was predictive of better outcomes among outpatients but not those in aftercare treatment for alcoholism.…”
Section: ) Transtheoreticalmentioning
confidence: 99%